1916 N.Y. Laws 338-39, An Act to Amend the Penal Law, in Relation to the Selling or Possessing of Silencers for Firearms, ch. 137, § 1. - (:unkn) unknown (General Publisher, 1916)
A person who sells or keeps for sale, or offers, or gives or disposes of, or who shall have or carry concealed upon his person any instrument, attachment, weapon or appliance for causing the firing of any gun, revolver, pistol, or other firearms to be silent or intended to lessen or muffle the noise of the firing of any gun, revolver, pistol, or other firearms shall be guilty of a felony, punishable by imprisonment for not more than five years.
--
Keywords: SUPPRESSORS